Intellectual Property Rights and International R and D Competition - Scandizzo, Stefania (IMF Working Papers; Working Paper ;, 2001)
This paper examines a country's incentives for intellectual property rights (IPR) protection in a global trading environment. There is a time inconsistency problem intrinsic to IPR protection: ex ante strong protection is warranted to promote innovation, but once discovery takes place there is an incentive to lower protection. The sub optimal but time consistent policy involves an insufficient level of protection and, therefore, of innovation. In more technologically advanced economies reputational considerations may be sufficient to maintain strong protection. Otherwise a commitment mechanism, such as participation in the World Trade Organization, or, more controversially, some form of bilateral punishment, may be used.